درجة رضا أولياء الأمور عن الخدمات التي تقدمها رياض الأطفال بمحافظة اللاذقية في ضوء مبادئ إدارة الجودة الشاملة (التركيز على رضا المستفيدين، العلاقة بين الروضة والمجتمع المحلي) (مجلة جامعة اللاذقية - سلسلة الآداب والعلوم الانسانية, 2016)
هدف البحث إلى تعرف درجة الرضا عن الخدمات التي تقدمها رياض الأطفال بمحافظة اللاذقية في ضوء مبادئ إدارة الجودة الشاملة (التركيز على رضا المستفيدين، العلاقة بين الروضة والمجتمع المحلي) من وجهة نظر أولياء الأمور، وكذلك تعرف الفروق تبعاً للمتغيرات الآتية (تابعية الروضة، موقع الروضة، المستوى التعليمي للأب، المستوى التعليمي للأم). شملت العينة (408) ولي أمر للعام الدراسي 2012/2013، ولتحقيق هدف البحث صُممت استبانة احتوت (38) عبارة، توزعت إلى مجالين. أظهرت النتائج أن درجة رضا أولياء الأمور عن الخدمات التي تقدمها رياض الأطفال جاءت متوسطة، وأظهرت النتائج أيضاً عدم وجود فروق دالة إحصائياً بين متوسط إجابات أولياء الأمور حول درجة الرضا عن الخدمات التي تقدمها رياض الأطفال تعزى للمتغيرات (المستوى التعليمي للأب، المستوى التعليمي للأم، تابعية الروضة)، وكذلك عدم وجود فروق دالة إحصائياً عند متغير موقع الروضة عند مجال التركيز على رضا المستفيد، ووجود فروق دالة عند مجال علاقة الروضة بالمجتمع المحلي. ومن جوانب الضعف التي لا تراعيها الروضة هي عدم التواصل مع أولياء الأمور خاصة فيما يتعلق بالمستجدات التي تقوم بها الروضة، ومن المقترحات التي قدمت من قبل أفراد عينة البحث هي (التناسب بين الدوام في مؤسسات رياض الأطفال مع الدوام في المؤسسات الحكومية، وإقامة اجتماعات دورية لأولياء الأمور للاستفادة من آرائهم في تطوير أداء الروضة، وتوفير البناء الصحي للروضة)، ويرى الباحث ضرورة إجراء دراسات لوضع مقاييس واعتمادها لقياس مدى رضا أولياء الأمور عن الخدمات التي تقدمها الروضة لأطفالهم. A research to aim identification the extent of Total Quality Management Principles Application in the  Kindergarten  Institutions as viewed by directors, care takers and parents in Lattakia province. It besides, provide information related to how satisfied  parents are as beneficiary from the services offered by these institutions and to what extent these services meet their requirements and inspirations, according to variables (nature of kindergarten ownership, its location, the education level of both parent).This study covered (408) parents in the academic year 2012/2013, and to realize the objectives of this study we employed a questionnaire that contained 38 paragraphs. The results revealed that the degree of satisfaction of parents for services provided by kindergartens was moderate and that there are no statistically significant differences between average responses of parents for services offered by the kindergartens due to variables (education level of parents and ownership of kindergarten).This also applies to the kindergarten location with relation to the beneficiary satisfaction, and the existence of statistically significant differences related to the local community. The negative aspects related to the kindergarten are failure to communicate with parents regarding new strategies adopted by kindergarten, and with the proposals submitted by the individuals of the study sample regarding (coordinating the working hours in the kindergarten and that in government institutions where parents work, beside establishing periodical meetings for parents in order to gain benefit from their ideas regarding developing performance of the kindergartens beside arranging for healthy buildings and services in the kindergarten). The study proposes the need to perform further studies to establish standards and criteria to gauge and investigate the extent of satisfaction of parents regarding services offered by the kindergarten to their children.